Effect of intraoperative position in single-level transforaminal lumbar interbody fusion at the L4/5 level on segmental and overall lumbar lordosis in patients with lumbar degenerative disease. Issue 39 (September 2019) - Miyazaki, Masashi; Ishihara, Toshinobu; Abe, Tetsutaro; Kanezaki, Shozo; Notani, Naoki; Kataoka, Masashi; Tsumura, Hiroshi
Abstract : Abstract: The purpose of this study was to investigate the effect of intraoperative positions in single-level (L4–5) transforaminal lumbar interbody fusion (TLIF) on segmental and overall lumbar lordosis (LL) in patients with lumbar degenerative disease. Thirty-eight consecutive patients who had undergone single-segment (L4–5) TLIF with 0° polyetheretherketone (PEEK) cage and pedicle screw fixation were evaluated. Twenty patients underwent surgery on the four-poster type frame with hip flexion at 30° (Group I) and 18 patients were operated on a Jackson spinal table to adjust their hip flexion to 0° (Group II). Preoperative standing, intraoperative prone, and postoperative standing lateral radiographs were obtained in each patient. The overall and segmental LL were analyzed according to the position in which the patients were placed for their operation and results compared between Groups I and II. Intraoperative intervertebral segmental LL at L4–5 and L5–S1 was increased in Group II than in Group I, whereas postoperative intervertebral segmental LL at L4–5 (fused level) was increased LL. In Group I intraoperative intervertebral segmental LL at L4–5 did not achieve sufficient lordosis, whereas postoperative intervertebral segmental LL at L3–4 was increased. The overall spinal alignment was unaffected by the decreased segmental LL in the fused level owing to the compensation of the upper adjacent segments. The more the hip was extended intraoperatively, the more the segmental lordosis increased in the lower lumbar spine. Thus, selecting the appropriate surgical table and hip position are very important. Underachievement of segmental lordosis leads to the acceleration of upper adjacent segment load.